Leadless pacemakers as replacement for infected transvenous pacemakers: different strategies are feasible. (19th May 2022) - Breeman, KTN; Beurskens, NEG; Wilde, AAM; Tjong, FVY; Knops, RE
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Pacemaker infections have a high morbidity and mortality and are an indication for extraction. For reimplantation, leadless pacemakers (LPs) may be preferable due to a low chance of infection. Even more, early LP reimplantation in pacemaker-dependent patients would circumvent the need for temporary pacemakers. Methods: We included all patients with LP implantation before, simultaneously with, or after transvenous pacemaker extraction due to infection, between January 2013 and December 2021. Outcomes were assessed during standard follow-up visits. Results: 30 patients (mean age 81±8 years) were included, of which 19 (63%) had a pocket infection, 10 (33%) endocarditis and 1 (3%) a systemic infection without endocarditis (Table). LP implantation was successful in all and was performed before extraction in 2 patients (7%; 3 and 5 days before), simultaneously in 6 (20%) and after extraction in 22 (73%). There were 3 procedural complications: 2 femoral artery bleedings and one LP dislocation. Also, one patient with complete AV block and an initially stable escape rhythm had an in-hospital cardiac arrest due to asystole after transvenous pacemaker extraction, but before LP implantation. During follow-up of median 21 months (IQR 7-53 months), no reinfection occurred. Six Nanostims were extracted due to early battery depletion, prophylactically after the battery advisory, or due to non-capture (median 36 months [range 0-67 months] after implantation); histopathologic examination of tissues around the devices showed no signs of infection. Two Nanostims were abandoned after which another device was implanted. No further device revisions were necessary during follow-up. Conclusions: In case of transvenous pacemaker infection, LP implantation before, simultaneously with or after extraction is safe and effective.